2021
DOI: 10.3390/plants10102100
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Genetic Factors Affecting Apospory Expressivity in Diploid Paspalum rufum

Abstract: In angiosperms, gametophytic apomixis (clonal reproduction through seeds) is strongly associated with polyploidy and hybridization. The trait is facultative and its expressivity is highly variable between genotypes. Here, we used an F1 progeny derived from diploid apomictic (aposporic) genotypes of Paspalum rufum and two F2 families, derived from F1 hybrids with different apospory expressivity (%AES), to analyze the influence of the environment and the transgenerational transmission of the trait. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 97 publications
(147 reference statements)
0
5
0
Order By: Relevance
“…Previous studies identified relevant factors influencing this competition in favor of the sexual or apomictic pathways. These factors can be gathered in numerous groups: polyploidy [2,9,23,27,48]; hybridization [2,48]; sexual pathway deregulation [14,49]; differential gene expression in the ovule [2,8,14,30,31,50]; inbreeding depression [31]; genetic disharmony in seminal tissues [51][52][53] (i.e., EBN, imprinting); light regime [11,23]; water stress [9,25]; environmental conditions [10,41]; seasonal variation of the flowering time [23,24]; pollination timing [28,54]; precocious development and parthenogenesis [21,30,31,48,55,56]. Studies suggest that a combination of all or some of these factors may be at play, affecting the reproductive pathways in the ovule [57].…”
Section: Becoming a Seed: The Advantages Of Aposporic Embryo Sacsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies identified relevant factors influencing this competition in favor of the sexual or apomictic pathways. These factors can be gathered in numerous groups: polyploidy [2,9,23,27,48]; hybridization [2,48]; sexual pathway deregulation [14,49]; differential gene expression in the ovule [2,8,14,30,31,50]; inbreeding depression [31]; genetic disharmony in seminal tissues [51][52][53] (i.e., EBN, imprinting); light regime [11,23]; water stress [9,25]; environmental conditions [10,41]; seasonal variation of the flowering time [23,24]; pollination timing [28,54]; precocious development and parthenogenesis [21,30,31,48,55,56]. Studies suggest that a combination of all or some of these factors may be at play, affecting the reproductive pathways in the ovule [57].…”
Section: Becoming a Seed: The Advantages Of Aposporic Embryo Sacsmentioning
confidence: 99%
“…are agamic complexes composed of sexual diploids (2n = 2x = 20) and facultative apomictic tetraploids (2n = 4x = 40) [38][39][40]. Previous studies in Paspalum species established that genetic or epigenetic background, ploidy levels, as well as environmental factors, influence the observed rates of apomixis and sexuality [23,24,31,41]. On one hand, diploids of Paspalum are able to produce aposporous embryo sacs, but seeds are only sexually produced [27,39,[42][43][44], although low rates of functional apomixis were recently noticed [45,46].…”
Section: Introductionmentioning
confidence: 99%
“…As can be noticed, and as postulated by Kumar (2017), the epigenetic control of apomixis is an emerging theory, with growing evidence (Karunarathne et al, 2020;Mateo de Arias, 2015;Podio et al, 2014;Rios et al, 2013;Soliman et al, 2021) in several species. Epigenetic changes and alterations in gene expression, particularly through DNA methylation, provide a means to achieve desirable phenotypic plasticity and adaptive advantages (Kumar et al, 2019).…”
Section: Discussionmentioning
confidence: 89%
“…The epigenetic control of apomixis expression is an emerging theory that suggests that apomixis is reversibly superimposed upon sexuality (Kumar, 2017). Although there is evidence of epigenetic control of the reproductive mode in several Poaceae species (Karunarathne et al, 2020;Reutemann et al, 2022;Rios et al, 2013;Soliman et al, 2021), the environmental influence on apospory/sexual expression throughout the flowering season has been scarcely explored in buffel grass (Gounaris et al, 1991;Hussey et al, 1991) under field conditions. Buffel grass is a protogynous (Shafer et al, 2000) and mainly cross-pollinated (Hanselka et al, 2004) species with variable levels of self-compatibility.…”
Section: Crop Sciencementioning
confidence: 99%
“…Transcriptome-wide changes at the onset of apomixis have been documented in several apomictic species (Hand and Koltunow 2014 ) and a global decrease in gene expression at the early stages of development in apomictic versus sexual individuals has been recorded in Boechera divaricarpa (Sharbel et al 2010 ), Hypericum perforatum (Galla et al 2017 ), Eragrostis curvula (Rodrigo et al 2017 ; Garbus et al 2019 ) and Paspalum Rufum (Soliman et al 2021 a, b). Transcriptional profiling of Arabidopsis embryos demonstrated that heterochrony of specific transcripts is more significant than spatial regulation (Spencer et al 2007 ), suggesting that timing of gene expression is critical in early development.…”
Section: Introductionmentioning
confidence: 99%